2017
DOI: 10.1097/md.0000000000007991
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between lumbar neuromuscular function and pain, lumbar disability in patients with nonspecific low back pain

Abstract: This study aims to examine the correlations between lumbar neuromuscular function and pain, lumbar disability in patients with nonspecific low back pain (NSLBP).Ninety patients, with ages 18 to 37 years old, with NSLBP were recruited in this study. The lumbar neuromuscular function was tested by the CON-TREX multijoint isokinetic test and training machine. This study uses the visual analog scale (VAS) and Roland-Morris Disability Questionnaire (RMDQ) to evaluate the pain and the dysfunction index of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Decreased lumbar proprioception may lead to higher sports injury risk, an increase in pain intensity, and lumbar disability. A negative correlation between lumbar proprioception and pain was described in our previous study [20].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Decreased lumbar proprioception may lead to higher sports injury risk, an increase in pain intensity, and lumbar disability. A negative correlation between lumbar proprioception and pain was described in our previous study [20].…”
Section: Introductionsupporting
confidence: 53%
“…In our previous cross-sectional study, we found that decreased lumbar muscle strength, endurance, and lumbar proprioception of the lumbar vertebra lead to an increase in pain intensity and lumbar disability [20]. Therefore, we hypothesized that patients with poor proprioceptive sense might have more clinical benefit from performing WBV exercises.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, proprioception sense was tested within 5 min after the smartphone use, which is a safe testing duration before the recovery of muscle and proprioception following muscle fatigue [28,29]. As pain severity and proprioception deficits are correlated [5], the Changes between baseline and post-task assessment for the tested task duration b…”
Section: Discussionmentioning
confidence: 99%
“…It has a lifetime prevalence of 85.5%, with 3.9 to 10.2% of the patients develop chronic low back pain (CLBP) [1,2]. Patients suffer from pain, impaired proprioception and reduced back mobility and function [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The alterations of the motor control of the deep local muscles of the lumbopelvic region and persistent arthrogenic muscle inhibition of lumbar multifidus result in segmental instability of the lumbar spine and, consequently, in recurrent back pain. [7][8][9][10][11][12] If the alterations in one or more of the spine's stabilising mechanisms do not resolve during the acute period, tissue damage is caused that causes LBP persist. 8 Numerous studies have shown that specific exercises aimed at local lumbar muscles result in improvements in pain and disability, as well as a lower incidence of recurrence and absenteeism in the chronic LBP population.…”
Section: Open Accessmentioning
confidence: 99%